Ensino de geografia em classes inclusivas com alunos com deficiência visual: estratégias didático-pedagógicas que permeiam as práticas docentes - Santos, Juliana Oliveira dos (2022)
Studying in regular schools is a right of people with disabilities that is expressed in Brazilian legislation, however, this right has still been the subject of questioning and lack of compliance. In view of this, currently, studies and debates that deal not only with the right of access, but, above all, with the right to permanence and learning of these school subjects, are highlighted. In this perspective, this research intended to understand the didactic-pedagogical strategies adopted by geography teachers in the mediation of teaching with visually impaired students, in inclusive classes in Feira de Santana, and the possible implications for teaching/learning. Qualitative research of the action research type was used in this work, it considers the reality and the difficulties encountered. In data collection, semi-structured interviews and pedagogical intervention through thematic workshops were used. Thus, geography teachers and visually impaired students from inclusive classes were consulted to identify such practices and verify the implications for the teaching and learning of geographic content. Also, workshops were held with tactile cartographic resources aimed at teaching and learning this curricular component for students with visual impairments. The research findings point to the existence of barriers that prevent the inclusion of these students, such as attitudinal, methodological, physicalarchitectural, communicational. It was also identified that the geographical education of students is hindered by the fragile mediation and resources that the school offers. In this way, it is necessary to increase investments, research and claims so that rights are transposed from the law to everyday school practice.